An Approach to Identifying Headache Patients That Require Neuroimaging - Micieli, Andrew; Kingston, William (Frontiers in Public Health, 2019)
Headache is one of the most common clinical scenarios faced by a neurologist or neurologist in training. However, the decision process on when to complete neuroimaging can be difficult in clinical practice. This article focuses on a well-organized and evidence-based approach to identify patients with headache that require neuroimaging and will lend confidence to the clinician faced with these scenarios in clinical practice. The approach includes neuroimaging in episodic migraine, chronic migraine, identifying secondary headache disorders in clinic and the emergency department, and discusses pitfalls to over imaging. The article concludes with a flowchart to summarize an overall clinical approach.